High-achieving Latino students : successful pathways toward college and beyond - Paik, Susan J.; Kula, Stacy M.; González, Jeremiah J.; González, Veronica V. (Emerald Publishing Limited : Information Age Publishing, inc., 2020)
"High-Achieving Latino Students: Successful Pathways Toward College and Beyond addresses a long-standing need for a book that focuses on the success factors of Latino students in the US. Much of the research focuses on the failure of Latino students or uses a deficit lens; this book uses a strength-based framework to understand and support Latino achievement. The book represents a step forward in maximizing their potential and development. As the Latino population continues to grow, high achievement is necessary for individual and national success. The authors acknowledge early preparation is key to successful pathways towards higher education. With a comprehensive approach, they propose best practices grounded in research and their experience in schools with Latino populations. The book chapters illuminate: (a) contextual factors surrounding Latino students' lives and identities, such as race, class, culture as well as social, historical, or other related issues; (b) alterable factors that support high achievement, such as raising educational expectations, increasing learning time, developing key relationships (e.g., parents, teachers, mentors, peers), and creating strong school-family-community connections; and (c) other key resources, such as cultural, social, and other forms of capital. Educational researchers, policymakers, and practitioners including school leaders, teachers, counselors, and parents will understand "what works" as they gain insight into Latino students' lives, opportunities, and resources. The book provides research-based recommendations from early to later school years on how to enhance student learning, develop talents, promote resilience and other pro-social behavior, support healthy relationships, and collaborate with families, schools, and communities"-- Provided by publisher.
Keywords: Hispanic Americans -- Education.; Hispanic Americans -- Education, Higher.; Hispanic American students.; Hispanic American college students.; Academic achievement -- Social aspects -- United States.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; elektronické knihy; electronic books